Milan between neglect and frenzy: does TikTok Mundi’s Generation Z counter-narrate the city? (Altre Modernità, 2024)
The article aims to illustrate the research interests and outcomes of the call for videos and reels, “Raccontaci la tua Milano Mondo!”. This initiative, conducted within the framework of the project TikTok Mundi, encouraged high school students in Milan to portray their city through audiovisual content. An analysis of the 38 contributions received unveiled a perception of Milan as a hectic city, often viewed as dangerous or alienating. This initiative provided young people with a unique platform to express their thoughts and impressions freely, exposing a perception of Milan as seldom beautiful and liveable, but rather as a mere transit point. The article concludes with an examination of the audiovisual content produced, underscoring how this reflects not only the discomfort experienced by young people, but also their aspiration to change the status quo.
Keywords: Milan; Generation Z; self-representation; perception of the city; audiovisual content